Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Menabung Di Bank Syariah - Hamdani, Ahmad Syukron; Rammatullah, Salim; Lubis, Romatua; Hasibuan, Lempang (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2024)
The increasing quantity of sharia banking and the decreasing market share of sharia banking and Indonesia's population of more than 100 million people are a challenge in attracting customers' decisions to use sharia banking products. The aim of this research is to determine the influence of promotional mix, service quality, bank characteristics and physical objects of Islamic banks on customers' decisions to save at Islamic banks. The sample used by BRI Syariah KC Malang Soekarno Hatta bank customers was 75 respondents. The analytical method used is multiple linear regression. The aim is to determine the relationship between independent variables and dividend variables. The findings from this research show that there are three independent variables that have a significant effect on the dependent variable. Namely the promotional mix, bank characteristics and physical objects of Islamic banks. Furthermore, service quality has no significant effect. Based on the four variables used, the coefficient of determination is 68.3% and the remainder is influenced by variables not examined in this research.